Relationship between biofilm formation and antibiotic resistance of Klebsiella pneumoniae and updates on antibiofilm therapeutic strategies - Li, Lifeng; Gao, Xueyan; Li, Mingchao; Liu, Yuchun; Ma, Jiayue; Wang, Xiaolei; Yu, Zhidan; Cheng, Weyland; Zhang, Wancun; Sun, Huiqing; Song, Xiaorui; Wang, Zhaobao (Frontiers in Cellular and Infection Microbiology, 2024)
Klebsiella pneumoniae is a Gram-negative bacterium within the Enterobacteriaceae family that can cause multiple systemic infections, such as respiratory, blood, liver abscesses and urinary systems., which can cause a wide range of infections, such as respiratory system infection, bloodstream infection, liver abscess and urinary system infection. Antibiotic resistance is a global health threat and, K. pneumoniae warrants special attention due to its resistance to most modern day antibiotics currently used. Biofilm formation is a critical strategy obstruction that enhances the antibiotic resistance of K. pneumoniae., whereas However, knowledge of on the molecular mechanisms of biofilm formation and its relation with antibiotic resistance in K. pneumoniae is limited. Understanding the molecular mechanisms of biofilm formation and its correlation with antibiotic resistance is crucial for providing insights for the design of new drugs to control and treat biofilm-related infections. In this review, we summarize recent advances in genes contributing to the biofilm formation of K. pneumoniae, new progresses on the relationship between biofilm formation and antibiotic resistance, and the new therapeutic strategies targeting biofilms. Finally, we discuss future research prospects directions to better combat that target the biofilm formation and antibiotic resistance of this priority pathogen.